Powder for ferrite and magnetic ferrite

By using aluminosilicate glass sol and hydrothermal synthesis technology, the problems of high calcining temperature, large energy consumption and impurity generation in the preparation of magnetic ferrite are solved, and magnetic ferrite with high purity and high magnetization strength are calcined at 800°C.

CN119911988APending Publication Date: 2025-05-02HUIZHOU ANCI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510200365.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the existing magnetic ferrite preparation method, there are problems such as excessive calcining temperature, high energy consumption and easy generation of impurities.

Method used

Aluminosilicate glass sol and hydrothermal synthesis technology are used to form a reaction precursor through low-temperature hydrothermal reaction, followed by magnetic separation and sintering, and the calcination temperature is reduced to 800°C.

Benefits of technology

The calcination temperature is significantly reduced, the formation of Fe2O3 impurities is avoided, the purity and saturation magnetization of magnetic ferrite are improved, and the goal of high purity and high magnetization strength is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of magnetic ferrite synthesis, in particular to powder for ferrite and magnetic ferrite. The invention provides a method for preparing high-purity and high-magnetization-intensity magnetic ferrite through low-temperature calcination, aiming at the problems that the calcination temperature is too high, the energy consumption is large and impurities are easy to generate in the existing magnetic ferrite preparation method. Aluminosilicate glass sol and a hydrothermal synthesis technology are adopted; the aluminosilicate glass sol promotes grain growth and improvement of sintering density at low temperature, and optimizes crystallinity and purity of the magnetic ferrite; the hydrothermal synthesis method effectively controls the reaction conditions, improves the reaction efficiency of the material, further reduces the generation of impurities, and ensures the excellent performance of the magnetic ferrite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of magnetic ferrite synthesis, in particular to a powder used for ferrite and magnetic ferrite. Background Art

[0002] Magnetic ferrite materials are an important type of magnetic materials and are widely used in electronics, communications, sensors, energy storage devices and other fields. Ferrite materials have become a common basic material in permanent magnet materials, microwave absorption materials and high-frequency electronic devices due to their excellent magnetic properties, chemical stability and low cost. Especially nickel-zinc ferrite (Ni x Zn 1₋x Fe2O4), due to its good magnetic properties and adjustable electrical properties, plays an important role in applications such as high-frequency magnetic components and electromagnetic interference suppression.

[0003] In the traditional preparation process of ferrite materials, the calcination process is one of the key steps. The calcination temperature directly affects the crystal structure, magnetic properties and purity of the ferrite. According to existing research, traditional magnetic ferrites often need to be calcined at high temperatures above 1000°C to ensure that they form a stable ferrite phase (such as NiFe2O4, ZnFe2O4, etc.) and achieve good magnetic properties. However, this high-temperature calcination process not only leads to high energy consumption and increased production costs, but also may introduce more impurities, reducing the purity and magnetic properties of the final product. Therefore, how to obtain high-quality magnetic ferrite materials at lower calcination temperatures has become an important research direction in the current field of magnetic materials.

[0004] Traditional methods for preparing magnetic ferrites mainly include solid-phase method, sol-gel method, hydrothermal method, etc., among which the solid-phase method is one of the most commonly used methods. In the solid-phase method, raw material powders such as iron source, zinc source, and nickel source are fully mixed and calcined under high temperature conditions to form ferrite. However, the main problem with the solid-phase method is that the calcination temperature usually needs to reach above 1000°C, and an incomplete ferrite phase is easily formed during the process, producing a large amount of Fe2O3 impurities, which not only affect the magnetic properties of the material, but also increase energy consumption. In addition, high-temperature calcination may also cause the grains to be too large, affecting the microstructure and final magnetic properties of the magnetic material.

[0005] In order to improve the defects of the solid phase method, researchers have proposed technologies such as sol-gel method and hydrothermal method to reduce the calcination temperature and optimize the crystal structure and magnetic properties of ferrite. The sol-gel method controls the gelation process of the solution so that the metal ions form a uniform precursor at a lower temperature, and then calcine at a lower temperature to obtain ferrite. However, this method still faces problems such as high energy consumption during high-temperature sintering and high difficulty in process control.

[0006] As an emerging preparation method in recent years, the hydrothermal method uses an aqueous solution medium under high temperature and high pressure conditions to promote chemical reactions between metal ions and prepare ferrite materials at a lower temperature. Although the hydrothermal method can obtain higher purity and smaller grain size, its operation is complicated, the reaction conditions are strict, and a certain high-temperature calcination step is still required.

[0007] CN 114804231 A discloses a method for preparing ferrite powder, which comprises the following steps: preparing single crystal Fe3O4 particles by hydrothermal method; using the single crystal Fe3O4 particles as templates, preparing Fe3O4-metal M hydroxide complex, wherein the metal M is selected from any one or more metal elements other than alkali metals, alkaline earth metals, aluminum (Al), and iron (Fe), and the ions of the metal M can generate hydroxide precipitation under alkaline aqueous solution conditions; and finally sintering to obtain ferrite powder. Although the method can be calcined at 900°C to obtain magnetic ferrite, the obtained magnetic ferrite has poor performance. Summary of the invention

[0008] In view of the deficiencies in the prior art, the present invention provides a powder for ferrite and magnetic ferrite.

[0009] A method for preparing magnetic ferrite comprises the following steps: (1) Take 3.3-3.4 g of ferrous sulfate heptahydrate and dissolve it in 20 mL of water to obtain a ferrous sulfate aqueous solution; Take 0.058-0.062 g of nickel sulfate hexahydrate and dissolve it in 20 mL of water to obtain a nickel sulfate aqueous solution; Take 0.46-0.50 g of zinc nitrate hexahydrate and dissolve it in 20 mL of water to obtain a zinc nitrate aqueous solution; Take 5.9-6.0g of aluminum nitrate hexahydrate and 3.40-3.44g of sodium silicate and dissolve them in 20ml of water, adjust the pH to 11-12 with sodium hydroxide, stir and heat to 80-90°C for 1-2h, and cool to room temperature to obtain aluminosilicate glass sol; Dissolve potassium hydroxide in deionized water to obtain a 0.006-0.08 mol / L potassium hydroxide solution; (2) 20 mL of ferrous sulfate aqueous solution, 20 mL of nickel sulfate aqueous solution, 20 mL of zinc nitrate aqueous solution, and 0.8-0.9 mL of aluminosilicate glass sol obtained in step (1) are mixed and stirred, and the pH is adjusted to 8-9 with the potassium hydroxide solution obtained in step (1) to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 120-150° C. for 3-4 hours, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, and washed with water 2-3 times, washed with anhydrous ethanol 2-3 times, and dried to obtain a powder for ferrite; (3) The ferrite powder obtained in step (2) is placed in a sintering furnace, heated from room temperature to 800-900° C. at a rate of 3-5° C., and calcined at a constant temperature for 2-3 hours to obtain the magnetic ferrite.

[0010] Beneficial effects of the present invention: The present invention aims at the problems of too high calcination temperature, high energy consumption and easy generation of impurities in the existing magnetic ferrite preparation method, and provides a method for preparing high-purity and high-magnetization magnetic ferrite by low-temperature calcination. Compared with the traditional high-temperature calcination method requiring more than 1000°C, the present invention significantly reduces the calcination temperature, and can obtain high-purity and high-magnetization magnetic ferrite by calcination at 800°C, and effectively avoids the generation of Fe2O3 impurities, and improves the saturation magnetization of the material. The key technical innovation lies in the use of aluminosilicate glass sol and hydrothermal synthesis technology: aluminosilicate glass sol promotes grain growth and sintering density at low temperature, optimizes the crystallinity and purity of magnetic ferrite; the hydrothermal synthesis method effectively controls the reaction conditions, improves the reaction efficiency of the material, further reduces the generation of impurities, and ensures the excellent performance of magnetic ferrite. The experimental results show that the magnetic ferrite obtained by calcining at 800°C of the present invention not only has high purity, but also has a saturation magnetization of 90.1 emu / g, which is significantly better than the conventional method or the comparative example without aluminosilicate glass sol. In addition, the present invention further optimizes the low-temperature sintering process by adjusting the dosage and ratio of aluminosilicate glass sol, thereby improving the performance of the final product. Therefore, the present invention provides a new, low-temperature, and efficient method for preparing magnetic ferrite, which has strong technical innovation and significantly surpasses the limitations of the prior art. DETAILED DESCRIPTION

[0011] Ferrous sulfate heptahydrate, CAS number: 7782-63-0.

[0012] Nickel sulfate hexahydrate, CAS number: 10101-97-0.

[0013] Zinc nitrate hexahydrate, CAS number: 10196-18-6.

[0014] Aluminum nitrate hexahydrate, CAS number: 25838-59-9.

[0015] Sodium silicate, CAS number: 1344-09-8.

[0016] Example 1 A method for preparing magnetic ferrite comprises the following steps: (1) Take 3.34 g of ferrous sulfate heptahydrate and dissolve it in 20 mL of water to obtain a ferrous sulfate aqueous solution; Take 0.06 g of nickel sulfate hexahydrate and dissolve it in 20 mL of water to obtain a nickel sulfate aqueous solution; Take 0.48 g of zinc nitrate hexahydrate and dissolve it in 20 mL of water to obtain a zinc nitrate aqueous solution; Take 5.95g of aluminum nitrate hexahydrate and 3.42g of sodium silicate and dissolve them in 20ml of water, adjust the pH to 12 with sodium hydroxide, stir and heat to 85°C for 1.5h, and cool to room temperature to obtain aluminosilicate glass sol; Dissolve potassium hydroxide in deionized water to obtain a 0.007 mol / L potassium hydroxide solution; (2) 20 mL of ferrous sulfate aqueous solution, 20 mL of nickel sulfate aqueous solution, 20 mL of zinc nitrate aqueous solution, and 0.85 mL of aluminosilicate glass sol obtained in step (1) are mixed and stirred, and the pH is adjusted to 8 with the potassium hydroxide solution obtained in step (1) to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 140° C. for 3 h, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, and washed with water 3 times, washed with anhydrous ethanol 3 times, and dried to obtain a powder for ferrite; (3) The ferrite powder obtained in step (2) is placed in a sintering furnace, heated from room temperature to 800° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0017] Example 2 A method for preparing magnetic ferrite comprises the following steps: (1) Take 3.34 g of ferrous sulfate heptahydrate and dissolve it in 20 mL of water to obtain a ferrous sulfate aqueous solution; Take 0.06 g of nickel sulfate hexahydrate and dissolve it in 20 mL of water to obtain a nickel sulfate aqueous solution; Take 0.48 g of zinc nitrate hexahydrate and dissolve it in 20 mL of water to obtain a zinc nitrate aqueous solution; Take 5.95g of aluminum nitrate hexahydrate and 3.42g of sodium silicate and dissolve them in 20ml of water, adjust the pH to 12 with sodium hydroxide, stir and heat to 85°C for 1.5h, and cool to room temperature to obtain aluminosilicate glass sol; Dissolve potassium hydroxide in deionized water to obtain a 0.007 mol / L potassium hydroxide solution; (2) 20 mL of ferrous sulfate aqueous solution, 20 mL of nickel sulfate aqueous solution, 20 mL of zinc nitrate aqueous solution, and 0.85 mL of aluminosilicate glass sol obtained in step (1) are mixed and stirred, and the pH is adjusted to 8 with the potassium hydroxide solution obtained in step (1) to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 140° C. for 3 h, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, and washed with water 3 times, washed with anhydrous ethanol 3 times, and dried to obtain a powder for ferrite; (3) The ferrite powder obtained in step (2) is placed in a sintering furnace, heated from room temperature to 750° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0018] Example 3 A method for preparing magnetic ferrite comprises the following steps: (1) Take 3.34 g of ferrous sulfate heptahydrate and dissolve it in 20 mL of water to obtain a ferrous sulfate aqueous solution; Take 0.06 g of nickel sulfate hexahydrate and dissolve it in 20 mL of water to obtain a nickel sulfate aqueous solution; Take 0.48 g of zinc nitrate hexahydrate and dissolve it in 20 mL of water to obtain a zinc nitrate aqueous solution; Take 5.95g of aluminum nitrate hexahydrate and 3.42g of sodium silicate and dissolve them in 20ml of water, adjust the pH to 12 with sodium hydroxide, stir and heat to 85°C for 1.5h, and cool to room temperature to obtain aluminosilicate glass sol; Dissolve potassium hydroxide in deionized water to obtain a 0.007 mol / L potassium hydroxide solution; (2) 20 mL of ferrous sulfate aqueous solution, 20 mL of nickel sulfate aqueous solution, 20 mL of zinc nitrate aqueous solution, and 0.85 mL of aluminosilicate glass sol obtained in step (1) are mixed and stirred, and the pH is adjusted to 8 with the potassium hydroxide solution obtained in step (1) to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 140° C. for 3 h, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, and washed with water 3 times, washed with anhydrous ethanol 3 times, and dried to obtain a powder for ferrite; (3) The ferrite powder obtained in step (2) is placed in a sintering furnace, heated from room temperature to 850° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0019] Example 4 A method for preparing magnetic ferrite comprises the following steps: (1) Take 3.34 g of ferrous sulfate heptahydrate and dissolve it in 20 mL of water to obtain a ferrous sulfate aqueous solution; Take 0.06 g of nickel sulfate hexahydrate and dissolve it in 20 mL of water to obtain a nickel sulfate aqueous solution; Take 0.48 g of zinc nitrate hexahydrate and dissolve it in 20 mL of water to obtain a zinc nitrate aqueous solution; Take 5.95g of aluminum nitrate hexahydrate and 3.42g of sodium silicate and dissolve them in 20ml of water, adjust the pH to 12 with sodium hydroxide, stir and heat to 85°C for 1.5h, and cool to room temperature to obtain aluminosilicate glass sol; Dissolve potassium hydroxide in deionized water to obtain a 0.007 mol / L potassium hydroxide solution; (2) 20 mL of ferrous sulfate aqueous solution, 20 mL of nickel sulfate aqueous solution, 20 mL of zinc nitrate aqueous solution, and 0.85 mL of aluminosilicate glass sol obtained in step (1) are mixed and stirred, and the pH is adjusted to 8 with the potassium hydroxide solution obtained in step (1) to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 140° C. for 3 h, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, and washed with water 3 times, washed with anhydrous ethanol 3 times, and dried to obtain a powder for ferrite; (3) The ferrite powder obtained in step (2) is placed in a sintering furnace, heated from room temperature to 900° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0020] Comparative Example 1 A method for preparing magnetic ferrite comprises the following steps: (1) Take 3.34 g of ferrous sulfate heptahydrate and dissolve it in 20 mL of water to obtain a ferrous sulfate aqueous solution; Take 0.06 g of nickel sulfate hexahydrate and dissolve it in 20 mL of water to obtain a nickel sulfate aqueous solution; Take 0.48 g of zinc nitrate hexahydrate and dissolve it in 20 mL of water to obtain a zinc nitrate aqueous solution; Dissolve potassium hydroxide in deionized water to obtain a 0.007 mol / L potassium hydroxide solution; (2) 20 mL of ferrous sulfate aqueous solution, 20 mL of nickel sulfate aqueous solution and 20 mL of zinc nitrate aqueous solution obtained in step (1) are mixed and stirred, and the pH is adjusted to 8 with the potassium hydroxide solution obtained in step (1) to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 140° C. for 3 h, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, and washed with water 3 times, washed with anhydrous ethanol 3 times, and dried to obtain a powder for ferrite; (3) The ferrite powder obtained in step (2) is placed in a sintering furnace, heated from room temperature to 800° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0021] Comparative Example 2 A method for preparing magnetic ferrite comprises the following steps: (1) 3.34 g of ferrous sulfate heptahydrate, 0.06 g of nickel sulfate hexahydrate, 0.48 g of zinc nitrate hexahydrate, 0.25 g of aluminum nitrate hexahydrate, and 0.14 g of sodium silicate were mixed to obtain a powder for ferrite; (3) The ferrite powder obtained in step (1) is placed in a sintering furnace, heated from room temperature to 800° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0022] Comparative Example 3 A method for preparing magnetic ferrite comprises the following steps: (1) 3.34 g of ferrous sulfate heptahydrate, 0.06 g of nickel sulfate hexahydrate, and 0.48 g of zinc nitrate hexahydrate were mixed to obtain a powder for ferrite; (3) The ferrite powder obtained in step (1) is placed in a sintering furnace, heated from room temperature to 800° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0023] Comparative Example 4 A method for preparing magnetic ferrite comprises the following steps: (1) Take 3.34 g of ferrous sulfate heptahydrate and dissolve it in 20 mL of water to obtain a ferrous sulfate aqueous solution; Take 0.06 g of nickel sulfate hexahydrate and dissolve it in 20 mL of water to obtain a nickel sulfate aqueous solution; Take 0.48 g of zinc nitrate hexahydrate and dissolve it in 20 mL of water to obtain a zinc nitrate aqueous solution; Take 5.95g of aluminum nitrate hexahydrate and 3.42g of sodium silicate and dissolve them in 20ml of water, adjust the pH to 12 with sodium hydroxide, stir and heat to 85°C for 1.5h, and cool to room temperature to obtain aluminosilicate glass sol; Dissolve potassium hydroxide in deionized water to obtain a 0.007 mol / L potassium hydroxide solution; (2) 20 mL of ferrous sulfate aqueous solution, 20 mL of nickel sulfate aqueous solution, 20 mL of zinc nitrate aqueous solution, and 0.7 mL of aluminosilicate glass sol obtained in step (1) are mixed and stirred, and the pH is adjusted to 8 with the potassium hydroxide solution obtained in step (1) to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 140° C. for 3 h, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, and washed with water 3 times, washed with anhydrous ethanol 3 times, and dried to obtain a powder for ferrite; (3) The ferrite powder obtained in step (2) is placed in a sintering furnace, heated from room temperature to 800° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0024] Comparative Example 5 A method for preparing magnetic ferrite comprises the following steps: (1) Take 3.34 g of ferrous sulfate heptahydrate and dissolve it in 20 mL of water to obtain a ferrous sulfate aqueous solution; Take 0.06 g of nickel sulfate hexahydrate and dissolve it in 20 mL of water to obtain a nickel sulfate aqueous solution; Take 0.48 g of zinc nitrate hexahydrate and dissolve it in 20 mL of water to obtain a zinc nitrate aqueous solution; Take 5.95g of aluminum nitrate hexahydrate and 3.42g of sodium silicate and dissolve them in 20ml of water, adjust the pH to 12 with sodium hydroxide, stir and heat to 85°C for 1.5h, and cool to room temperature to obtain aluminosilicate glass sol; Dissolve potassium hydroxide in deionized water to obtain a 0.007 mol / L potassium hydroxide solution; (2) 20 mL of ferrous sulfate aqueous solution, 20 mL of nickel sulfate aqueous solution, 20 mL of zinc nitrate aqueous solution, and 0.95 mL of aluminosilicate glass sol obtained in step (1) are mixed and stirred, and the pH is adjusted to 8 with the potassium hydroxide solution obtained in step (1) to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 140° C. for 3 h, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, and washed with water 3 times, washed with anhydrous ethanol 3 times, and dried to obtain a powder for ferrite; (3) The ferrite powder obtained in step (2) is placed in a sintering furnace, heated from room temperature to 800° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0025] Comparative Example 6 A method for preparing magnetic ferrite comprises the following steps: (1) Take 3.34 g of ferrous sulfate heptahydrate and dissolve it in 20 mL of water to obtain a ferrous sulfate aqueous solution; Take 0.06 g of nickel sulfate hexahydrate and dissolve it in 20 mL of water to obtain a nickel sulfate aqueous solution; Take 0.48 g of zinc nitrate hexahydrate and dissolve it in 20 mL of water to obtain a zinc nitrate aqueous solution; Take 6.1g of aluminum nitrate hexahydrate and 3.42g of sodium silicate and dissolve them in 20ml of water, adjust the pH to 12 with sodium hydroxide, stir and heat to 85°C for 1.5h, and cool to room temperature to obtain aluminosilicate glass sol; Dissolve potassium hydroxide in deionized water to obtain a 0.007 mol / L potassium hydroxide solution; (2) 20 mL of ferrous sulfate aqueous solution, 20 mL of nickel sulfate aqueous solution, 20 mL of zinc nitrate aqueous solution, and 0.85 mL of aluminosilicate glass sol obtained in step (1) are mixed and stirred, and the pH is adjusted to 8 with the potassium hydroxide solution obtained in step (1) to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 140° C. for 3 h, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, and washed with water 3 times, washed with anhydrous ethanol 3 times, and dried to obtain a powder for ferrite; (3) The ferrite powder obtained in step (2) is placed in a sintering furnace, heated from room temperature to 800° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0026] Comparative Example 7 A method for preparing magnetic ferrite comprises the following steps: (1) Take 3.34 g of ferrous sulfate heptahydrate and dissolve it in 20 mL of water to obtain a ferrous sulfate aqueous solution; Take 0.06 g of nickel sulfate hexahydrate and dissolve it in 20 mL of water to obtain a nickel sulfate aqueous solution; Take 0.48 g of zinc nitrate hexahydrate and dissolve it in 20 mL of water to obtain a zinc nitrate aqueous solution; Take 5.8g of aluminum nitrate hexahydrate and 3.42g of sodium silicate and dissolve them in 20ml of water, adjust the pH to 12 with sodium hydroxide, stir and heat to 85°C for 1.5h, and cool to room temperature to obtain aluminosilicate glass sol; Dissolve potassium hydroxide in deionized water to obtain a 0.007 mol / L potassium hydroxide solution; (2) 20 mL of ferrous sulfate aqueous solution, 20 mL of nickel sulfate aqueous solution, 20 mL of zinc nitrate aqueous solution, and 0.85 mL of aluminosilicate glass sol obtained in step (1) are mixed and stirred, and the pH is adjusted to 8 with the potassium hydroxide solution obtained in step (1) to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 140° C. for 3 h, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, and washed with water 3 times, washed with anhydrous ethanol 3 times, and dried to obtain a powder for ferrite; (3) The ferrite powder obtained in step (2) is placed in a sintering furnace, heated from room temperature to 800° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0027] Comparative Example 8 A method for preparing magnetic ferrite comprises the following steps: (1) Take 3.34 g of ferrous sulfate heptahydrate and dissolve it in 20 mL of water to obtain a ferrous sulfate aqueous solution; Take 0.06 g of nickel sulfate hexahydrate and dissolve it in 20 mL of water to obtain a nickel sulfate aqueous solution; Take 0.48 g of zinc nitrate hexahydrate and dissolve it in 20 mL of water to obtain a zinc nitrate aqueous solution; Take 6.84g of sodium silicate and dissolve it in 20ml of water, and adjust the pH to 12 with sodium hydroxide, stir and heat to 85℃ for 1.5h, and cool to room temperature to obtain silicate glass sol; Dissolve potassium hydroxide in deionized water to obtain a 0.007 mol / L potassium hydroxide solution; (2) 20 mL of ferrous sulfate aqueous solution, 20 mL of nickel sulfate aqueous solution, 20 mL of zinc nitrate aqueous solution, and 0.85 mL of silicate glass sol obtained in step (1) are mixed and stirred, and the pH is adjusted to 8 with the potassium hydroxide solution obtained in step (1) to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 140° C. for 3 h, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, and washed with water 3 times, washed with anhydrous ethanol 3 times, and dried to obtain a powder for ferrite; (3) The ferrite powder obtained in step (2) is placed in a sintering furnace, heated from room temperature to 800° C. at a rate of 4° C., and calcined at a constant temperature for 2 h to obtain the magnetic ferrite.

[0028] Test Example 1: The saturation magnetization intensity of the magnetic ferrite obtained in each embodiment and comparative example was tested with reference to GB / T 22580-2008 “Test method for properties of ferrite permanent magnet materials”.

[0029] Table 1: Magnetization performance test results Test Example 2 The composition of the magnetic ferrite obtained in each embodiment and comparative example was analyzed by XRD Table 2: Composition of magnetic ferrite It can be seen from Table 1 and Table 2 that the magnetic ferrites prepared in Example 1 (calcination temperature of 800°C), Example 3 (calcination temperature of 850°C), and Example 4 (calcination temperature of 900°C) of the present invention have high purity and large saturation magnetization, indicating that the ferrite powder prepared according to the scheme of the present invention can be calcined at 800°C to obtain a magnetic ferrite material with excellent performance. Compared with the traditional magnetic ferrite material which requires high-temperature calcination of more than 1000°C, the preparation scheme of the present invention significantly reduces the calcination temperature and improves the saturation magnetization of the obtained magnetic ferrite. Comparing Example 2 (calcination temperature of 750°C) with Example 1, it is shown that when calcined at a temperature below 800°C, Fe2O3 impurities will be generated, which will affect the performance of the obtained magnetic ferrite.

[0030] Comparison Example 1, Comparison Example 2, Comparison Example 3 and Example 1 are compared, wherein Comparison Example 1 differs from Example 1 in that no aluminosilicate glass sol is added; Comparison Example 2 differs from Example 1 in that solid phase direct calcination is adopted; Comparison Example 3 differs from Example 1 in that no aluminosilicate glass sol is added, and solid phase direct calcination is adopted; it can be seen that the magnetic ferrites obtained in Comparison Example 1, Comparison Example 2, and Comparison Example 3 are much lower than those in Example 1 in terms of saturation magnetization and purity, which indicates that aluminosilicate glass sol plays an important role in promoting the low-temperature sintering of magnetic ferrites, and the steps of first hydrothermally synthesizing ferrite powder and then calcining play an extremely important role in the purity and performance of the obtained magnetic ferrite.

[0031] Compared with Example 1, Comparative Example 4 uses a lower amount of aluminosilicate glass sol than Example 1. Compared with Example 1, Comparative Example 5 uses a higher amount of aluminosilicate glass sol than Example 1. Compared with Example 1, Comparative Example 6 and Comparative Example 7 adjust the ratio of aluminum ions to silicon ions in the aluminosilicate glass sol. Compared with Example 1, Comparative Example 8 changes the aluminosilicate glass sol into silica sol. Compared with Example 1, the saturation magnetization of Comparative Examples 4-8 is reduced, and impurities are generated to a certain extent, which shows that the aluminosilicate glass sol plays a vital role in the process of low-temperature calcination synthesis of magnetic ferrite, and the change in the addition amount of aluminosilicate glass sol and the change in the ratio of silicon to aluminum ions also have an important influence on the performance of the magnetic ferrite finally obtained.

[0032] In summary, the present invention aims at the problems of too high calcination temperature, high energy consumption and easy generation of impurities in the existing magnetic ferrite preparation method, and provides a method for preparing high-purity and high-magnetization magnetic ferrite by low-temperature calcination. Compared with the traditional high-temperature calcination method requiring more than 1000°C, the present invention significantly reduces the calcination temperature, and can obtain high-purity and high-magnetization magnetic ferrite by calcining at 800°C, and effectively avoids the generation of Fe2O3 impurities, and improves the saturation magnetization of the material. The key technical innovation lies in the use of aluminosilicate glass sol and hydrothermal synthesis technology: aluminosilicate glass sol promotes grain growth and sintering density at low temperature, optimizes the crystallinity and purity of magnetic ferrite; the hydrothermal synthesis method effectively controls the reaction conditions, improves the reaction efficiency of the material, further reduces the generation of impurities, and ensures the excellent performance of magnetic ferrite. The experimental results show that the magnetic ferrite obtained by calcining at 800°C of the present invention not only has high purity, but also has a saturation magnetization of 90.1 emu / g, which is significantly better than the conventional method or the comparative example without aluminosilicate glass sol. In addition, the present invention further optimizes the low-temperature sintering process by adjusting the dosage and ratio of aluminosilicate glass sol, thereby improving the performance of the final product. Therefore, the present invention provides a new, low-temperature, and efficient method for preparing magnetic ferrite, which has strong technical innovation and significantly surpasses the limitations of the prior art.

[0033] Of course, the above description is only a specific embodiment of the present invention and is not intended to limit the scope of implementation of the present invention. All equivalent changes or modifications made according to the structure, characteristics and principles described in the patent application scope of the present invention should be included in the patent application scope of the present invention.

Claims

1. A method for preparing ferrite powder, characterized in that: The following steps are involved: An aqueous solution of ferrous sulfate, an aqueous solution of nickel sulfate, an aqueous solution of zinc nitrate, and an aluminosilicate glass sol are mixed and stirred, and the pH is adjusted to 8-9 with a potassium hydroxide solution to obtain a reaction precursor, and the reaction precursor is subjected to a hydrothermal reaction at 120-150° C. for 3-4 hours, cooled to room temperature, magnetically separated using an electromagnet or a permanent magnet, washed with water 2-3 times, washed with anhydrous ethanol 2-3 times, and dried to obtain a powder for ferrite.

2. The method for preparing ferrite powder according to claim 1, characterized in that: The method for preparing the ferrous sulfate aqueous solution comprises the following steps: taking 3.3-3.4 g of ferrous sulfate heptahydrate and dissolving it in 20 mL of water to obtain the ferrous sulfate aqueous solution.

3. The method for preparing ferrite powder according to claim 1, characterized in that: The method for preparing the nickel sulfate aqueous solution comprises the following steps: taking 0.058-0.062 g of nickel sulfate hexahydrate and dissolving it in 20 mL of water to obtain the nickel sulfate aqueous solution.

4. The method for preparing ferrite powder according to claim 1, characterized in that: The method for preparing the zinc nitrate aqueous solution comprises the following steps: taking 0.46-0.50 g of zinc nitrate hexahydrate and dissolving it in 20 mL of water to obtain the zinc nitrate aqueous solution.

5. The method for preparing ferrite powder according to claim 1, characterized in that: The preparation method of the aluminosilicate glass sol comprises the following steps: dissolving 5.9-6.0 g of aluminum nitrate hexahydrate and 3.40-3.44 g of sodium silicate in 20 ml of water, adjusting the pH to 11-12 with sodium hydroxide, stirring and heating to 80-90° C. for reaction for 1-2 hours, and cooling to room temperature to obtain the aluminosilicate glass sol.

6. The method for preparing ferrite powder according to claim 1, characterized in that: The method for preparing the potassium hydroxide solution comprises the following steps: dissolving potassium hydroxide in deionized water to obtain a 0.006-0.08 mol / L potassium hydroxide solution.

7. A powder for ferrite, characterized in that: The powder is prepared by the method for preparing the ferrite powder as described in claims 1 to 6.

8. A magnetic ferrite, characterized in that: The ferrite powder as claimed in claim 7 is calcined to obtain the ferrite, wherein the specific steps of the calcination are: placing the ferrite powder in a sintering furnace, heating it from room temperature to 800-900°C at a rate of 3-5°C, and calcining it at a constant temperature for 2-3h to obtain the magnetic ferrite.